(untitled) (Research, Society and Development, 2022)
The main objective of this article is to characterize the phenomenon of feminization in a Polyclinic in the Sanitary District IV of Recife. Data was collected from the servers through the unit’s human resources, and a literature review of the last 5 years on the subject was carried out. It was evidenced that 78% of the professionals who carry out work activities in the base unit of the study are female. It was characterized that 53% of these women have an undergraduate degree. 75% of women have a statutory employment contract, 52% of women work 30 hours a week and 74% earn between two and six monthly gross minimum wages. It was concluded that the study can contribute for managers to promote work spaces with physical structures that meet the comfort needs of women health workers, and for governments to rethink the salary policy for women in health and in Brazil, since they are the majority on many labor fronts.